مدى إدراك مستهلكي المواد الغذائية لممارسات الغش والخداع التسويقي دراسة ميدانية في مدينة اللاذقية - شيخ ديب صلاح; قاسم سامر; مرتكوش نور منير (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى التعرف على مدى إدراك مستهلكي المواد الغذائية لممارسات الغش والخداع التسويقي في مجالات السلعة والسعر والترويج والتوزيع, ودراسة الفروق في مستوى إدراكهم لهذه الممارسات وفق متغيرات الجنس والعمر والمؤهل العلمي. ولتحقيق أهداف البحث تمّ بناء استبانة وتوزيعها على (271) مستهلك في مدينة اللاذقية, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: يدرك مستهلكي المواد الغذائية في مدينة اللاذقية ممارسات الغش والخداع التسويقي المتعلقة بالسلعة والسعر والترويج والتوزيع بدرجة كبيرة. لا توجد فروق جوهرية ذات دلالة معنوية بمستوى إدراك مستهلكي المواد الغذائية في مدينة اللاذقية لممارسات الغش والخداع التسويقي وفق متغيرات الجنس والعمر. توجد فروق جوهرية ذات دلالة معنوية بمستوى إدراك مستهلكي المواد الغذائية في مدينة اللاذقية لممارسات الغش والخداع التسويقي وفق متغير مستوى التعليم, حيث يزداد إدراك المستهلكين لهذه الممارسات في المستويات العلمية المتقدمة. This research aims to identify the range of awareness of fraud practices and deception in the areas of marketing item, price, promotion and distribution, and to study the differences in the level of awareness of these practices according to variables of gender, age and academic qualification. To achieve the objectives of the research, a questionnaire is designed and distributed to (271) consumers in Lattakia City. After deep analysis and study, the following conclusions have been reached: The consumers in Lattakia City are fully aware of fraud and deceit regarding the product, price, promotion and distribution. There are no statistically significant differences among the levels of food consumers’ awareness of the practices of fraud and deceit regarding the variables of gender and age. There are statistically significant differences in the levels of food consumers’ awareness of practices of fraud and deceit regarding the variable of academic qualification. The higher their academic qualifications are, the more the consumers are aware of these practices.